2009
DOI: 10.1055/s-0029-1210818
|View full text |Cite
|
Sign up to set email alerts
|

Intraindividual Comparison of Pharmacokinetics of Insulin after Intravenous, Portal, Subcutaneous and Peritoneal Administration

Abstract: To compare the kinetics of praehepatic and of posthepatic administered insulin, short term insulin deprived diabetic dogs were sequentially injected with 200 mU/kg of a monocomponent porcine insulin using either the intravenous, portal, subcutaneous or peritoneal route. After peritoneal insulin was applied, the peripheral plasma insulin levels increased immediately, their maxima were in the same range as after subcutaneous injection but the duration of elevation was shorter. There were portal-peripheral insuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Taken together, previous studies have shown that in insulin-dependent diabetic subjects kept normoglycemic, the flux rates of alanine and hepatic glycogen storage are normalized by long-term prehepatic but not by posthepatic insulin administration (28) and that neutral regular purified insulin is rapidly enough absorbed from the peritoneal site to allow for its feedback-controlled infusion (27). It has been demonstrated here that such feedback control appears manageable, indeed, when the control parameters are adapted to the particular pharmacokinetics of this route.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…Taken together, previous studies have shown that in insulin-dependent diabetic subjects kept normoglycemic, the flux rates of alanine and hepatic glycogen storage are normalized by long-term prehepatic but not by posthepatic insulin administration (28) and that neutral regular purified insulin is rapidly enough absorbed from the peritoneal site to allow for its feedback-controlled infusion (27). It has been demonstrated here that such feedback control appears manageable, indeed, when the control parameters are adapted to the particular pharmacokinetics of this route.…”
Section: Resultsmentioning
confidence: 65%
“…The animals were instrumented with a chronic peritoneal catheter, which was in place over 2 * 1 months and whose tip was attached to the splenic hilus and whose end was led out on the back via a subcutaneous tunnel. Production of diabetes, animal handling, and the general experimental procedure have been described before (27). The interval between two successive experiments in a given animal was between 3 and 10 days.…”
Section: Methodsmentioning
confidence: 99%
“…The slow glucose lowering effect after SC insulin delivery, even with fast acting insulins (27), is considered the greatest challenge to a subcutaneous AP system. Delivering insulin in the IP space provides a faster effect compared to SC delivery (28), and resembles the normal physiologic situation when pancreas secretes insulin into the portal vein (29)(30)(31)(32). By moving both the glucose sensing and hormone delivery of the AP into the IP space, it is possible to improve both glucose sensing and insulin dynamics.…”
Section: Consequences Of the Hypothesismentioning
confidence: 99%
“…The peritoneal lining is permeable to water, small solutes, and proteins 22 and after IP delivery, a portion of the glucagon will diffuse through the visceral peritoneum and be transported directly to the liver via the portal vein. This route of drug delivery has been described for insulin showing a fast and efficient absorption to the portal vein and a fast effect on the BGL 23,24 . We hypothesize that glucagon delivered by the IP route reaches the liver earlier and at a high concentration and induces a fast and large glucose response because the IP route resembles normal glucagon secretion, i.e.…”
Section: Discussionmentioning
confidence: 99%